Claudia and the phantom phone calls - Martin, Ann M., 1955- (Martin, Ann M., 1955- Baby-sitters Club, 2020)
When Kristy, Claudia, Mary Anne, and Stacey, the members of the Baby-sitters Club, each receive mysterious calls while they are working, they decide to find out who is responsible.